Didactic planning based on the current context, a fundamental axis for the development of competencies - Calics Salcedo, Lorena Patricia (2021)
This article is intended to show the relevance of competencies in the current context. The age of the knowledge society (where globalization imposed new demands) leads to a shift in education and learning for learners. in order to respond efficiently to the changes that are constantly taking place in the world in which one lives immersed. This whole situation obliges us to transform the educational systems in one way or another, it is precisely where the need for contextualized and competency-based didactic planning is envisioned, allowing the training of reflective, productive, flexible, creative and competitive individuals, It also contribute to strengthening in them the importance of learning to live together and to forging values that will help them to perform in the best way in the twenty-first century; thus achieving their self-realization, which leads to their enjoyment of total emancipation